Loki. The complete first season [videorecording (Blu-Ray)] - Waldron, Michael, 1987- (Marvel Studios, 2023)
Marvel Studios' Loki features the God of Mischief as he steps out of his brother's shadow. Set after the events of Avengers: Endgame, this action-packed, time-defying thriller stars Tom Hiddleston as the title character, with Owen Wilson as agent Mobius.